Sectoral and skill contributions to labor productivity in Asia - Matthias Helble; Trinh Q. Long; Trang T. Le (Asian Development Bank Institute (ADBI), 2019)
Using a decomposition approach on data collected by the Asian Productivity Organization (APO) as well as World Input-Output data, we show that in most Asian economies the services sector makes the largest contribution to labor productivity. Furthermore, we find evidence of a major reallocation of labor from agriculture directly to services, bypassing the manufacturing sector. This finding challenges the traditional view that countries in their economic development need to have their workforce employed first in manufacturing before switching to services. Lastly, the paper studies how different skill levels contribute to labor productivity growth. We find that high-skilled workers have contributed most to overall labor productivity growth in developing Asia. In services, high-skilled workers have mainly driven labor productivity, indicating that upskilling and training are instrumental in services-led development.
Keywords: O11; J21; 330; labor productivity; manufacturing; services; skills